INTEGRATING SPATIAL MAPPING AND SOCIO-CULTURAL DYNAMICS FOR SUSTAINABLE ECOTOURISM MANAGEMENT AT GOA ERGENDANG: A GEO-ANTHROPOLOGICAL STUDY IN DELI SERDANG REGENCY - Mita Nalsalisa Br Barus; Vadillah Raihto Hutasuhut; Muhammad Najmul Fahmi; Angelo Arevalo Simanullang; Annisa Oktavira; M Faoug Ghazali Matondang (USN Kolaka, 2025)
Goa Ergendang, a unique geo-cultural site in Deli Serdang, Indonesia, possesses significant ecotourism potential, including natural hot springs, stalactites, and rich local folklore (the Umang mythos). However, its development is severely hindered by informal community self-management, poor infrastructure, and a critical lack of spatial information for visitors. This research aims to (1) identify the fundamental challenges in its sustainable management and (2) formulate an integrated management model based on a geo-anthropological approach. This study employed a mixed-method design, integrating quantitative spatial analysis (GIS) with qualitative socio-cultural analysis. Methods included GIS mapping for accessibility, topography, and potential zoning, combined with in-depth interviews with local managers, stakeholders, and visitors. The findings reveal four primary challenges: (1) weak institutional capacity due to informal management, leading to resource limitations and poor heritage protection (e.g., the destruction of the